The Construction of Bisexual Act as A Ground for Divorce on Critical Legal Studies Perspective - Sulistianingsih, Lilis (Islamic Family Law Department, Sharia and Law Faculty, UIN Sunan Ampel Surabaya, Indonesia, 2023)
Bisexuality as an orientation deviation that places a person to be able to have sexual relations both against the opposite sex and the same sex, today has become a social problem as well as a legal issue that seems to be still not expressly regulated in the legislation. Especially if bisexual acts are committed in a legal marriage institution by a husband or wife, while in it there are no constant quarrels. This article discusses bisexual acts committed in marriage with two focuses of discussion, namely bisexual acts in legislation from the perspective of critical legal studies (CLS) and legal reformulation of future laws and regulations. Through the type of normative research with legal, philosophical, and conceptual approaches, this article argues that the normativity of bisexual acts in marriage from the CLS perspective is still a requirement for an individualist-liberal legal style. The article argues that a reformulation of some regulations in Indonesia is necessary. This article offers a reformulation with two things. First, adding the offense of same-sex adultery to Article 411 to Article 411A of the Criminal Code. Second, amend and add authentic interpretations to the Explanation of Article 39 paragraph (2) of Law Number 1 of 1974 concerning Marriage, Article 19 letter a of Government Regulation Number 9 of 1975 concerning the Implementation of Law Number 1 of 1974 concerning Marriage, and Article 116 letter a of the Compilation of Islamic Law.